Influence of environmental effect on thermal and mechanical properties of welded PPS/carbon fiber laminates - Araújo, Izabely Gonçalves [UNESP]; P Santos, Luis F. [UNESP]; Marques, Luis F.B. [UNESP]; Reis, Jonas F. [UNESP]; B De Souza, Samia Danuta [UNESP]; Botelho, Edson C. [UNESP] (IOP Publishing, 2019)
This work consists in the evaluation of the influence of the environmental effects (ultraviolet radiation and humidity) on PPS/carbon fiber thermoplastic composite laminates integrated by electrical resistance welding. In order to evaluate how welding and conditioning influence the properties of the composite, the following tests were performed: Dynamic-Mechanical Analyze (DMA) and Thermomechanical Analyze (TMA) to evaluate the working temperature of the material, the Iosipescu test and Interlaminar shear test (ILSS) to evaluate interlaminar fracture strength and the Double Cantilever Beam (DCB) and End Notched Flexure (ENF) were used to analyze interlaminar fracture toughness. Considering the presented results, both the hygrothermal and UV conditioning did not promote such relevant modifications in the laminate structure, except for the DCB evaluation, which showed a reduction of approximately 53% in relation to the GIc of the unconditioned samples. Another factor also analyzed was that welding did not promote significant reductions in the thermal and mechanical properties of the laminates.
Keywords: carbon fiber; electrical resistance welding; PPS; thermoplastic composites